2020
DOI: 10.1108/jidob-05-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative case report: participatory action research into using EQUIP to support community discharge

Abstract: Purpose There is a need to evaluate an adapted Equipping Youth to help One Another (EQUIP) programme for people with intellectual disabilities and forensic needs. The purpose of this paper is to explore a service user’s experience of completing the intervention as part of their transition into the community. Design/methodology/approach A collaborative case report was used. Following hospital discharge and completion of the adapted EQUIP programme, one service user with mild intellectual disability was suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Within most studies ( n = 12), lived‐experience researchers were involved in the development of interview and/or focus group questions. Some went further, stating that people with lived experience were involved in the conceptualisation of the study (Crabtree et al., 2016; Erickson et al., 2022; Janssen et al., 2017; Tearle et al., 2020). Others reported that lived‐experience researchers were involved in applying for ethical approval (McLeod et al., 2020) or project managing the study (Forsyth et al., 2017, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within most studies ( n = 12), lived‐experience researchers were involved in the development of interview and/or focus group questions. Some went further, stating that people with lived experience were involved in the conceptualisation of the study (Crabtree et al., 2016; Erickson et al., 2022; Janssen et al., 2017; Tearle et al., 2020). Others reported that lived‐experience researchers were involved in applying for ethical approval (McLeod et al., 2020) or project managing the study (Forsyth et al., 2017, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In some projects academic researchers completed the analysis independently, consulting with the lived‐experience researchers (to review and verify) before finalising the results (Abram et al., 2020; Edge et al., 2020; McLeod et al., 2020; Yu & Hope House Men and Alumni, 2018). Other papers cited that the analysis was completed primarily by lived‐experience researchers with support from academic researchers (Desai, 2019; Perrett et al., 2020) or completed together (Crabtree et al., 2016; Janssen et al., 2017; Tearle et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations